Kompresi Record Database MySL Dengan Menerapkan Algoritma Goldbach Code G1 - Ainal Azhar (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2022)
In this digital era, everything is digitally based and many applications have been created to make work easier or serve as a means of entertainment. Some applications that exist today have a database as a place to store data. Currently the database that is still often used is MySQL, this is because MySQL is an open source database server application. The data in the database is called records, the more records stored, the larger the size of the database. Data compression is the process of encoding information using bits or other information-carrying units that are less than representative of data that is not encrypted by a particular encoding system test results on the system that the Record file size is smaller after compression. Compression ratio results obtained on average above 94%, decompression ratio obtained on average above 5%, Space Saving obtained on average above 6%